Regional absorptive capacity and regional disparities in Lithuania: linkages, evidences and insights - Juknevičienė, Vita (Univerzita Pardubice, 2017)
Regions face contemporary challenges of global economy and modern society and act differently. Therefore, regional disparities occur in various fields: social welfare, economic growth, infrastructure developments, etc. Sometimes the regional retardation (as a reflection of regional disparities) inhibits the progress and brings losses; sometimes otherwise, it encourages the flexibility and the implementation of new ideas. Especially retarding regions, seeking for socio-economic welfare, must search for new (specific, adapted to the context and circumstances) ways of acting. Indisputably innovations become the core of a socio-economic progress in all regions. And the development of absorptive capacity (individual, organizational, regional) as a main precondition for any innovative activity, leading to innovations, could create favorable preconditions to gain the competitive advantage. Therefore, this article draws linkages between levels of regional absorptive capacity and regional welfare by giving some evidences from Lithuania (a small European country). It argues that regional absorptive capacity can be understood as a cause and a consequence of the regional development process and be reflected by regional disparities. Results of the research illustrate the mutual connection: region with better socio-economic results has more possibilities to develop its absorptive capacity and to reach its higher level, needed for future development.
Keywords: regional absorptive capacity; innovation; regional development; O31; R11